Marginal Adaptation and Microleakeage of Directly and Indirectly Made Fiber Reinforced Composite Inlays - Ovul, Kumbuloglu (Bentham Open, 2011)
AIM: This study evaluated in vitro microleakage of inlays made by direct or indirect techique with or without fiber reinforced composite (FRC) substructure. MATERIALS AND METHODS: Standardized mesio-occlusal cavities were prepared and restored using direct-technique with composite resin only or FRC-composite resin, and indirect technique with laboratory composite only or FRC-laboratory composite resin. After thermocycling, teeth were immersed in basic fuchsin dye, sectioned and examined under a stereo-microscope (x40). RESULTS: No differences of cement thickness and dye penetration were found in gingival area (p>0.05), whereas microleakage revealed statistical differences between groups (p=0.02) in occlusal area, where FRC-groups had lower microleakage than composite restorations. Thickness of cement layer did not show significant difference between groups with indirect technique (p>0.05). CONCLUSION: The present study suggests that insertion of FRC substructure to the inlay cavity by direct composite filling technique does not increase the marginal leakage compared to that of cementing indirectly made restotorations by composite resin luting cement. CLINICAL SIGNIFICANCE: On the basis of the results of this in vitro study, the use of direct FRC technique might be an effective way to decrease the marginal leakage.